2017
DOI: 10.1038/s41598-017-10169-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro blood cell viability profiling of polymers used in molecular assembly

Abstract: Biocompatible polymers have been extensively applied to molecular assembly techniques on a micro- and nanoscale to miniaturize functional devices for biomedical uses. However, cytotoxic assessments of developed devices are prone to partially focus on non-specific cells or cells associated with the specific applications. Thereby, since toxicity is dependent on the type of cells and protocols, we do not fully understand the relative toxicities of polymers. Additionally, we need to ensure the blood cell biocompat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 45 publications
3
55
0
2
Order By: Relevance
“…HA containing hydrogels and coated surfaces are nonadhesive due to their high hydrophilicity, but incorporating PLL as the last layer has been shown to aid cells in adhering . Despite their uses in cell culture, it is well known that polycations, including PLL, can be toxic to mammalian cells at high MW and concentrations . Our results indicated that while NIH 3T3 fibroblasts incubated in media exposed to PLL 30 and PLL 90 coatings remained similarly viable to untreated controls, cells exposed to media incubated in PLL 400 coatings over 24 h lost viability (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…HA containing hydrogels and coated surfaces are nonadhesive due to their high hydrophilicity, but incorporating PLL as the last layer has been shown to aid cells in adhering . Despite their uses in cell culture, it is well known that polycations, including PLL, can be toxic to mammalian cells at high MW and concentrations . Our results indicated that while NIH 3T3 fibroblasts incubated in media exposed to PLL 30 and PLL 90 coatings remained similarly viable to untreated controls, cells exposed to media incubated in PLL 400 coatings over 24 h lost viability (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…61,93 Despite their uses in cell culture, it is well known that polycations, including PLL, can be toxic to mammalian cells at high MW 114 and concentrations. [115][116][117] Our results indicated that while NIH 3T3 fibroblasts incubated in media exposed to PLL 30 and PLL 90 coatings remained similarly viable to untreated controls, cells exposed to media incubated in PLL 400 coatings over 24 h lost viability (Fig. 8).…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, at higher [PDDA], PDDA molecules that did not combine with BFS would attach to the cells exerting their cytotoxic activity. The hemolytic activity of PDDA was reported as important only above [PDDA] = 1 mg·mL −1 [29,33,53].…”
Section: Cytotoxicity Of Pdda/ova Nps Against Mammalian Cells In Culturementioning
confidence: 99%
“…In summary, cationic micro and nanoparticles are effectively taken up both by macrophages and dendritic cells since electrostatic attraction promotes particle binding and subsequent internalization [11,14,20,24,25]. Cationic particles and liposomes containing dioctadecyldimethylammonium bromide (DODAB) cationic lipid [13,26] carrying Mycobacterium tuberculosis [13,27], Chlamydia trachomatis [11], or Neisseria meningitides antigens enhanced the cellular and humoral immune response against them [16,28].Another important class of cationic adjuvants is represented by the cationic polymers despite their overt cytotoxicity [29][30][31][32][33]. They easily combine with oppositely charged proteins [34].…”
mentioning
confidence: 99%
See 1 more Smart Citation